THE Implementation of Integrated Quality Management in Education Institutions - Siti Patmawati; Valin Mertianti Dewi; Masduki Asbari; Ipang Sasono; Agus Purwanto (AGUSPATI RESEARCH INSTITUTA, 2023)
Implementation of Integrated Quality Management needs to be done in educational institutions as a form of efforts to improve the quality of education. This study discusses the implementation of Integrated Quality Management in educational institutions and the problems and solutions that occur in its implementation in educational institutions. the. In carrying out the educational process, it will not be separated from improvements in accordance with the problems faced every year or in accordance with the implementation of TQM in schools which has the main goal of providing satisfaction for internal and external education customers, services with quality product results. Implementation of Integrated Quality Management in Indonesia requires at least three stages of implementation, namely: preparation, planning, and implementation. Barriers to the implementation of Total Quality Management in Indonesia include resistance to change, lack of commitment to quality, and lack of readiness, willingness and human competence. Alternative solutions are necessary informed about the importance of change in achieving quality, maintaining and developing it, so that a shared commitment to quality grows.